The Application of Domestication and Foreignization Strategies in Translating Arabic-English Collocations in Awlad Haratina’s Novel (International Journal of Language, Literacy and Translation, 2025)
This paper examines the translations of collocations in a literary text in light of the translation strategies used. This paper examines the translations of collocations in a literary text in light of the translation strategies used within the framework of Venuti's foreignization and domestication strategies. The study aims to examine the translation strategies that are frequently employed to translate collocations. It also attempts to find out if the translators of the TTs follow Venuti’s preferred strategy of translation, foreignization. Moreover, it investigates if using these strategies resulted in any distortion of the SL message. Accordingly, a comparative quantitative analysis and an expressive interpretive examination are followed to analyze the collected data. The study reveals that foreignization is highlighted by the heavy usage of literal translation, cultural borrowing and descriptive equivalence procedures. Domesticating procedures are manifested in cultural equivalent, addition, reduction, omission and adaption. According to the nearly equal percentage of using the two strategies, the study results in finding that collocations can be translated by using the two strategies, domestication and foreignization depending on the type of the collocation. However, foreignization strategy is used as the most frequent strategy to translate collocations.